EPIC STAR : a reliable and efficient approach for phonon- and impurity-limited charge transport calculations - Deng, Tianqi (2021)
A computationally efficient first-principles approach to predict intrinsic semiconductor charge transport properties is proposed. By using a generalized Eliashberg function for short-range electron–phonon scattering and analytical expressions for long-range electron–phonon and electron–impurity scattering, fast and reliable prediction of carrier mobility and electronic thermoelectric properties is realized without empirical parameters. This method, which is christened “Energy-dependent Phonon- and Impurity-limited Carrier Scattering Time AppRoximation (EPIC STAR)” approach, is validated by comparing with experimental measurements and other theoretical approaches for several representative semiconductors, from which quantitative agreement for both polar and non-polar, isotropic and anisotropic materials is achieved. The efficiency and robustness of this approach facilitate automated and unsupervised predictions, allowing high-throughput screening and materials discovery of semiconductor materials for conducting, thermoelectric, and other electronic applications.